The role of immunotherapy in Guillain-Barré syndrome: understanding the mechanism of action - Shahrizaila, N.; Yuki, N. (Informa Healthcare, 2011)
Guillain-Barré syndrome (GBS) is the most frequent cause of acute flaccid paralysis and, despite treatment, there continues to be an associated mortality and severe disability ranging from 9 to 17%. This article reviews the rationale behind the existing immunotherapy in GBS and discusses the future direction that work in this area should follow. AREAS COVERED: The pathogenesis of GBS and the current evidence for the different forms of immunotherapy in GBS are reviewed. The proposed mechanism of action of each treatment--(steroids, plasma exchange and intravenous immunoglobulin (IVIG))--in GBS are discussed. EXPERT OPINION: Both plasma exchange and IVIG are equally effective in GBS although the latter is preferred in view of its ease of access and lower rates of complications. Although not clinically established, there may be a role for the concomitant use of steroids with IVIG and, in patients with severe disease and poor prognostic scores, plasma exchange followed by IVIG or two successive IVIG may prove beneficial.